Epicardial fat and the risk of atrial tachy-arrhythmia recurrence post pulmonary vein isolation: a computed tomography study - Goldenberg, Gustavo R.; Hamdan, Ashraf; Barsheshet, Alon; Neeland, Ian; Kadmon, Ehud; Yavin, Hagai; Omelchenko, Alex; Erez, Aharon; Marcuschamer, Ilan; Kornowski, Ran; Strasberg, Boris; Golovchiner, Gregory (The International Journal of Cardiovascular Imaging, 2021)
Epicardial and Pericardia fat have been hypothesized to exert local and systemic pathogenic effects on nearby cardiac structures. The present study aimed to evaluate the impact of epicardial and pericardial fat volumes on the outcome of patients that underwent a first pulmonary vein isolation (PVI) with cryoablation. We included 130 consecutive patients with atrial fibrillation (AF) that underwent contrast enhanced ECG-gated cardiac computed tomography (CCT) before a PVI. The control group included 50 patients in normal sinus rhythm that underwent ECG-gated CT to rule out coronary artery disease. Epicardial and pericardial fat volumes were quantified with CCT. Patients with AF compared to patients with normal sinus rhythm (control group) had significantly larger epicardial (140.3 ± 58.1 vs. 55.9 ± 17.7 ml; respectively, P < 0.001) and pericardial (77.0 ± 35.5 ml vs. 27.2 ± 9.5 ml; respectively, P < 0.001) fat volumes. Among patients that underwent PVIs, those with AF recurrence had a greater epicardial (175.0 ± 54.4 ml vs. 130.7 ± SD 54.2 ml; respectively, P < 0.001) and pericardial (93.7 ± SD 42.8 vs. 72.5 ± SD 31.9 ml; respectively, P < 0.001) fat volumes, compared to patients with no AF recurrence. Multivariate analyses revealed that epicardial fat was an independent predictor of recurrence post-ablation (HR = 1.08, 95% CI 1.02–1.16 per 10-ml increase in volume; P = 0.009). Pericardial fat was associated with 7% increase in risk of recurrent AF (HR = 1.07, 95% CI 0.98–1.18; P = 0.117). Epicardial fat, assessed with contrast enhanced CCT, is an independent predictor of AF recurrence after PVI ablation.